Discover the Fun of Playing Music and Understanding Music Theory Using Flashcards - Fransisca Inneke Rossari; Dinny Devi Triana; Deden Haerudin (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to explore the effectiveness of flashcard media in music learning, especially in helping students understand music theory and increase motivation to play music through a fun and interactive approach. Using the Systematic Literature Review (SLR) method, this study identified, evaluated, and synthesized eight selected scientific articles published between 2015-2025. The selection process was based on PRISMA guidelines and Zawacki-Richter's SLR model, including the formulation of research questions, screening of articles based on inclusion and exclusion criteria, and assessment of study quality. The results showed that the use of flashcards - both in manual and digital form - consistently contributed positively to the improvement of rhythmic ability, understanding of notation concepts, and affective engagement of learners from various levels. Flashcards proved effective in simplifying complex musical material into concrete visual representations, strengthening long-term memory through retrieval practice and spaced repetition techniques. Furthermore, the integration of flashcards in project-based pedagogical approaches (PjBL), character learning, as well as digital technologies such as apps and AR, shows great potential in enriching music learning experiences that are inclusive, collaborative and meaningful. Therefore, this study recommends the continued development of interactive technology-based flashcard media as a future music learning innovation.